Liquid Power : Contested Hydro-Modernities in Twentieth-Century Spain - Swyngedouw, E. (Erik) (Book collections on Project MUSE., 2015)
Erik Swyngedouw explores how water becomes part of the tumultuous processes of modernisation and development. Using the experience of Spain as a lens to view the interplay of modernity and environmental transformation, he shows that every political project is also an environmental project. Offering an innovative perspective on the relationship of nature and society, 'Liquid Power' illuminates the political nature of nature.